Interactive Learning: Human Anatomy Mobile Application for Elementary Students - Sipahutar, Lahmudin; Handayani, Nursyah (International Journal of Computer and Information System (IJCIS), 2024)
Student has a different method. One interesting learning method that can increase student interest is by utilizing multimedia. Multimedia applications in learning methods are quite interesting because they contain colored images, sound and even animation. Learning using multimedia makes a student not very dependent on the presence of a teacher. Where a teacher or lecturer only acts as a mediator and facilitator who helps the learning process of students or students to run well. A researcher can be carried out correctly by choosing a method to guide research activities. The process of collecting data then analyzing the data to conclude the research results. Method of observation in data search by observing directly at the research object. The method involves asking teachers and students questions about the anatomy of the human body in science lessons. The library method is carried out by collecting information according to the topic of the problem. This Android-based human anatomy learning application program for elementary school students was created using Android Studio for the display and processes running in it. Based on the results of the research and discussion, it can be concluded that this mobile learning application for human body anatomy for elementary school children can be achieved using the MDLC (Multimedia Development Life Cycle) method which is carried out to the testing stage and using developer tests with the Black box testing method, so that the application Mobile-based learning for elementary school children.